Development Direction Study: old Age Insurance Program in Indonesia Through the Revision of Permenaker No. 2 of 2022 - Saragih*, Tarimantan Sanberto; Pramasanti, An Nisa; Mahaganti, Fergie Stevi; Fitriani, Kania; Augustin, Eldest (Riwayat: Educational Journal of History and Humanities, 2023)
Placing an Old Age Security (JHT) savings scheme within the National Social Security System with simple and easy rules for workers is not a simple matter. JHT savings involve very broad stakeholders (workers, employers, BPU (non-wage earners), fund managers and the government and involve very large long-term fund flows. The aim of this research is to explain the urgency of JHT management from a philosophical, juridical and sociological, as well as develop policy recommendations and good public communication management related to workers' retirement preparations. The method used is a descriptive qualitative approach with data collection carried out through literature studies from various sources of regulatory documents, interviews, and FGDs with stakeholders. This process is able to capture perspectives theoretical and empirical regarding the Old Age Security scheme in Indonesia by considering philosophical, juridical, sociological, and political aspects. Analysis of various information is placed within the framework of an aging society welfare perspective. The results of this research show that workers and individuals who are no longer active in the labor market work will still be able to maintain the level of welfare by utilizing the contributions accumulated while still actively working. Countries that adhere to a universal welfare scheme place JHT as part of the cushion to support the welfare of an aging society which can be seen from the avoidance of generations. who are no longer productive or who are not active in the world of work from vulnerability.